(untitled) (TAJ: Journal of Teachers Association, 2022)
Background: The study aimed to assess the importance of dental check-ups for preventing dental caries among children 5-12 years of age in Rajshahi. Materials & Methods: This descriptive study was conducted in Dental Unit, Rajshahi Medical College, Different Dental Clinics, Dental Chambers in Rajshahi City Corporation from January 2018 to December 2019. A total number of 370 participants were allocated to detect dental caries and history of visiting dental clinics or hospitals for a dental check-up. A cross-sectional survey using a self-structured questionnaire and clinical examination of the oral cavity were conducted among participants to detect dental caries. Results: 8.92% of participants visited dentists for a regular dental check-up, whereas 49.73% visited dentists only when they had pain or problems with their teeth. 40.81% of participants had dental caries who never visited dentists, and 47.57% of participants were suffering from dental caries who went to the dental clinic or hospital only when there were necessary or emergency. Conclusion: Regular dental check-up reduce the possibility of dental caries among children. TAJ 2021; 34: No-2: 90-94